An 89% solution adoption rate at a two-year follow-up: evaluating the effectiveness of an animated agricultural video approach. Issue 3 (2nd July 2020) - Bello-Bravo, Julia; Abbott, Eric; Mocumbe, Sostino; Maria, Ricardo; Mazur, Robert; Pittendrigh, Barry R.
ABSTRACT: Securing the adoption of scalable agro-educational information and communication technology (ICT) solutions by farmers remains one of the international development community's most elusive goals – in part due to two key gaps in the data: (1) limited comparisons of competing knowledge-delivery methods, and (2) few to no follow-ups on long-term knowledge retention and solution adoption. Addressing both of these gaps, this follow-up study measures farmer knowledge retention and solution adoption two years after being trained on an improved postharvest bean storage method in northern Mozambique. The results found animated-video knowledge delivery at least as effective as a traditional extension approach for knowledge retention (97.9%) and solution adoption (89%). As animated video can more cost-effectively reach the widest – even geographically isolated – populations, it readily complements extension services and international development community efforts to secure knowledge transfer and recipient buy-in for innovations. Implications and future research for adult learning are also discussed.